Meeting financial challenge facing China's Sponge City Program (SCP) – Hong Kong as a gateway to green finance - Faith Ka Shun Chan (Nature-Based Solutions, 2022)
China's Sponge City Program (SCP) envisions a city's surface water management system to function like a sponge to absorb, store, infiltrate, and purify rainwater, and release it for reuse when needed. It emphasizes the use of natural and natural-engineering hybrid measures to mimic natural water cycle, thus offers Nature-Based-Solutions (NBS) to urban surface water management. The SCP has become a flagship sustainability program, applied across 30 pilot cities in mainland China since 2014. Significant progress has been made with three years of start-up financial support from the central government. At present, securing adequate financial resources to support further construction, operation, and maintenance of relevant green/blue infrastructures becomes the key challenge to extending the SCP within pilot cities and to other cities. Green finance, referring to local, national, or transnational financial investments from public, private, and alternative sources flowing into environmental and sustainability initiatives, has been experimented in the EU member countries and identified as one of the key business models to NBS, could be a viable solution to further the uptake of China's SCP concept and its implementation. In this context, the emergence of Hong Kong as an Asia-Pacific green finance hub offers a gateway for the SCP to secure financial resources. This paper describes the financial challenge of the SCP and the emerging development of green finance in China and compares it with the EU's experience in NBS green finance. It then explores how Hong Kong could take advantage of its well-established international standards and favourable geopolitical position as a key financial hub to channel green capital into China's SCP from interested investors. To do so requires overcoming current barriers in financial regulations and jurisdictional regimes between mainland China and Hong Kong. A stable and transparent cross-border green finance platform should be established to actively engage investors interested in the SCP and other green projects, so as to accelerate China's transition towards its goal of ecological civilisation and sustainable development.